EXPLORING THE STUDENTS' SPEAKING ABILITY BASED ON THEIR DIFFERENT PERSONALITIES - Arma Dianti Putri; Aswadi Jaya; Marleni Marleni (Universitas PGRI Palembang, 2023)
The Purpose of the study was to analyze the students' different personalities and their speaking ability. The Methodology of this study was used qualitative descriptive method by using the triangulation such as interview, questionnaire and documentation. The result of the data shows us that there are 12 students as openness, 11 students as conscientiousness, 7 students as agreeableness, 6 students as neuroticism and 4 students only as extroverts. Then, the students' different personalities don't affect their speaking ability. Lastly, neuroticism is better in speaking English than other personalities. From this study, the writer found out that the big five personalities (extrovert, conscientiousness, openness, agreeableness and neuroexisted in IBA senior high school.